ANALYSIS OF FACTORS THAT AFFECT TO INFRASTRUCTURE IMPROVEMENT OF SYUKURAN AMINUDDIN AMIR AIRPORT IN BANGGAI DISTRICT - Sutrisno Mustaman; Fahira F; Nirmalawati (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2020)
The airport is one of the important infrastructures in the air transportation field that functions to provide aircraft flight services so that there is a need for compatibility between the fleet and its infrastructure, in this case improving the infrastructure of Syukuranan Aminuddin Amir (SAA) Airport. The aim of this study is to analyze the factors that influence the improvement of the infrastructure of SAA Airport. The location of the study was conducted at the SAA Airport, Banggai Regency, Central Sulawesi Province. Data collection was carried out by distributing questionnaires to 120 respondent passengers on airplanes who use the SAA airport. Data analysis using factor analysis methods. The analysis result shows there are 11 factors that affect infrastructure improvement of SAA Airport is socio-economic, airport service quality, operator service quality, flight traffic demand, air transport service demand, air transportation mode selection, airport departure facility (waiting room) and airplane ticket purchase decisions, parking area and waiting room, flight schedule and potential regional commodity yields, service and process baggage handling, and transportation accessibility to the airport.